Participatory Research Approaches in Times of Covid-19: A Narrative Literature Review. (19th April 2021) - Hall, Johanna; Gaved, Mark; Sargent, Julia
This review aims to collate and organize the current literature base on the use of participatory research methods within Covid-19 and pandemic contexts. Participatory approaches rely on establishing trust and rapport between researchers and participants and advocate actively involving participants in the planning, implementation and evaluation of a research issue. However, by transitioning such approaches to an online and geographically distributed context, the openness and equitability of participatory approaches may be reduced or lost. By providing an overview of current empirical and guidance literature on the use of participatory approaches within the context of Covid-19, this review not only offers a basis for how a variety of methods may be used and adapted to distanced contexts, but also explicates the challenges associated with the use of these methods and the wider methodological implications posed by the Covid-19 pandemic. Furthermore, this review outlines the issues associated with conducting this type of research more generally, providing implications for how distance-based participatory methods may be used in wider contexts where face-to-face interaction may not be appropriate, or fieldwork may be disrupted due to logistical reasons.